Millennial Dance Craze for The Well-Being of Teachers: A Multiple Case Study - Santos, Sahlee A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study was designed to determine the impact of secondary school teachers' engagement with the millennial dance craze on their teaching and their well-being. Observing teachers' coping mechanisms and factors on fitness, increasing workload demands while having active leisure and social connections, and promoting the importance of teachers' physical and mental well-being motivated the researcher to pursue the investigation on the secondary school teachers' engagement with the millennial dance craze. Qualitative procedures were employed in this case study. Results revealed that secondary teachers' participation in the millennial dance craze is essential since it demonstrates personal explorations and transformation as reflected from their assessment on how their engagement with the millennial dance craze have affected them. As a result, they come to value the millennial dancing craze, which aids teachers' emotional and social development as well as their physical and mental health by allowing them to explore other aspects of life. It is advised that secondary level teachers take part in all types of dances, not just millennial dances, as this will give them the chance to be active, boost their confidence, and learn other important life lessons.